The Description of Sources of Literary Heritage and Qori Zakir’s Life - Madgoziyev Iskandar Abduvosit o’g’li (Global Scientific Publishing, 2023)
The article is devoted to the research of sources related to the life and work of Qori Zakir Muhammadnazar ugli who is one of the representative of the Andijan literary atmosphere, in which the manuscript and printed sources related to the poet are fully described and the information is analyzed comparatively. The newly identified sources of the poet's work are given special scientific information
Keywords: literary atmosphere; manuscript; devon; autograph